Overview: Developing a high profit herd - John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 1986)
The present surplus of dairy products has led to a decrease in farm-level milk receipts. Future reductions in the federal milk price support program, together with a predictable increase in feed grain and protein supplement prices, dictates that only the efficient producers will survive. By exercising known management options in the areas of herd health, reproduction, and nutrition, dairymen can increase production per cow, decrease feed cost, and thereby, increase profitability. Major management efforts need to be directed toward replacement heifer programs, planned matings, estrous detection, care of the periparturient cow, sanitation, and allocation of concentrate among cows according to milk production. These efforts require only manager time. Other efforts, such as a preventive herd health program (PHHP), require an increase in operational cost but will result in substantial returns per dollar invested.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Feed cost; Production; Profitability; Reproduction; Nutrition